The Great Gatsby reimagined: Preservice English teachers' critical reading of the novel and graphic novel - Tekin, Eda; Ilhan, Genc Osman (WILEY, 2026)
This study investigates the critical reading experiences of preservice English teachers by comparing the original novel The Great Gatsby with its graphic novel adaptation. A total of 35 preservice teachers from the English Language Teaching Department participated. Over the course of a 14-week semester, both the novel and graphic novel were assigned sequentially, and comparative discussions were facilitated throughout the process. The study employed a mixed-methods approach, combining qualitative interviews with a quantitative Likert scale survey. The survey assessed various aspects of the texts, including narrative structure, character development, thematic representation and overall critical reading. The findings indicated that while preservice teachers appreciated the visual appeal and engaging nature of the graphic novel, they also observed a reduction in the depth and complexity of character portrayal compared to the original novel. The study emphasises the importance of incorporating diverse formats, such as graphic novels, into literary education. The findings suggest that graphic novels can make stories more engaging and easier to understand. However, they may also simplify complex themes and character development. This research highlights the need for further exploration of graphic novels as teaching tools, recognising their strengths in enhancing comprehension while also considering their challenges in preserving the depth and nuance of traditional narratives.
Keywords: comparative analysis; critical reading; graphic novel; preservice English teachers; The Great Gatsby; EFL CLASSROOM; NOVELS; LITERACY; COMPREHENSION; STUDENTS; MODEL; WORK; Education & Educational Research; Linguistics